Expansão do ensino superior privado em Alagoas: a contribuição do Programa Universidade Para Todos (PROUNI) - Azevedo Filho, Gabriel Soares de (2017)
This research proposes to analyze the Expansion of Private Higher Education in Alagoas and the contribution of the University for All Program (PROUNI). PROUNI was created on January 13, 2005 through Law No. 11,096, in the context of the discourse on the democratization of higher education, which had the objective of making access to higher education possible in private and non-profit institutions. We then sought to answer the following question: how did the University for All Program contribute to the expansion of private higher education in Alagoas? The objective of the research is to investigate the participation of PROUNI in the process of expansion of private higher education in Alagoas and its relationship with neoliberal policies, in the years 2009 to 2016. This work was characterized by a qualitative research, and, to support the studies, we opted for bibliographic and documentary research. We had categories of analysis such as higher education, expansion, Neoliberalism and PROUNI. During the course of the research, we interviewed important authors for the work: Trindade (1999, 2000), De Albuquerque Fávero (2006), Dourado (2002, 2003, 2011), Cunha (1980, 2000, 2003), Filgueiras, Santomé (2003), Leher (1998, 2004) and Verçosa and Cavalcante (2015). The systematizations of the data had as parameters the documents elaborated by the MEC / INEP, among them: Laws, Decrees, ordinances, manuals and reports. The design of the research was characterized by a historical panorama of higher education, as well as an analysis of Neoliberalism and its contribution in Brazilian educational public policies, and a study of PROUNI since its creation, its contribution to the expansion of private higher education, especially in the state of Alagoas. From the official data and its results, we infer that PROUNI has contributed to the development of private higher education in the state of Alagoas through the application of public money in private higher education institutions via scholarships for undergraduate studies in private HEIs. Thus, the research points out PROUNI as a federal government program that contributed to the expansion of private higher education in Alagoas.